Green E-Commerce: An Assessment of Market Readiness & Movement to a New Competitive Landscape - KESERWANI, DR HITESH; RASTOGI, DR HIMANSHU (The journal of contemporary issues in business and government, 2021)
With the expanding internet reachability and improved broadband connectivity options, the online business has also grown tremendously. The modern generation is more computer savvy and have got more choices than ever before. On the flip side, the online business platforms are also struggling to offer more attractive and innovative marketing ideas. In consideration to the current environmental challenges, it cannot be overlooked as how significant the aspect of sustainability is crucial at both e-tailer and the online consumer’s front. Today’s customers are socially aware, and they are also cautious about the companies operating procedures to which consumer purchases the things, as company should also follow ethical practices. Safeguarding environment is a major concern for the current generation customers. A study conducted by IBM and National Retail federation, it was found that almost 80% of customers across the globe reported that environmental sustainability was important factor for them, and they now prefer more to buy green products. Today’s e-commerce platforms are highly competitive in nature and companies are very keen to create a differentiating factor to stand out in the cut-throat competition of websites. One such marketing strategy which is largely adopted by the online retailers is to present themselves as environment-friendly website, where emphasizing the sustainability aspect and promoting this phenomenon of green e-commerce is a part of their pledge and commitment. This pledge acts as a new hit point in attracting more customers. The paper attempt to analyse the impact of green marketing in online customers and tries to explore factors which they consider in buying products from such websites.